Factors determining Outcomes in Hospitalized Patients with Acute Exacerbation of Chronic Obstructive Pulmonary Disease - Bam , Niraj; Sapkota , Dharmendra; Kuikel , Sandip (Journal of Institute of Medicine Nepal, 2023)
Introduction Acute exacerbation of chronic obstructive pulmonary disease (AECOPD) is frequently accompanied by increased local and systemic inflammation brought on by airway infection, pollution, or other airway insults. This study aimed to find the factors determining outcomes in patients hospitalized with acute exacerbation of COPD. Methods An analytical study among diagnosed cases of AECOPD was conducted. Bivariate regression model followed by Multinomial logistic regression (MNLR) was used to contrast outcome variables. A p-value less than 0.05 was considered statistically significant in all analyses. Results A total of 126 patients with a mean age of 72.04±9.75 years were included in the study. Most of the patients were current smokers or past smokers, cor-pulmonale was present in 34.9% of patients. The most common co-morbidity was hypertension(41.2%). Most (55.6%) patients had early discharge, 31.7% (40) patients had late discharge and 12.7% (16) patients had mortality as the outcome. After bivariate analysis, among all variables of the study qualified to be included in the multivariate MNLR model, Neutrophil Lymphocyte ratio (NLR) was found to be a significant predictor of late discharge in comparison with early discharge while Age and NLR were found to be a significant predictor of Mortality in comparison with late discharge among patients with AECOPD. Conclusions Higher the NLR longer, hospital stay (>5days vs <5days). Older Age and higher NLR predicted mortality in comparison to longer hospital stay (>5days). Since NLR is a common variable in both the outcome (early vs late discharge and late discharge vs mortality), NLR can be used to predict the outcome (early discharge, late discharge, and mortality) of patients with AECOPD.